Plant root plasticity during drought and recovery: What do we know and where to go? - Zheng, Congcong; Bochmann, Helena; Liu, Zhaogang; Kant, Josefine; Schrey, Silvia D.; Wojciechowski, Tobias; Postma, Johannes Auke (Frontiers in Plant Science, 2023)
Aims Drought stress is one of the most limiting factors for agriculture and ecosystem productivity. Climate change exacerbates this threat by inducing increasingly intense and frequent drought events. Root plasticity during both drought and post-drought recovery is regarded as fundamental to understanding plant stress resilience and maximizing production. We mapped the different research areas and trends that focus on the role of roots in plant response to drought and rewatering and asked if important topics were overlooked. Methods We performed a comprehensive bibliometric analysis based on journal articles indexed in the Web of Science platform from 1900-2022. We evaluated a) research areas and temporal evolution of keyword frequencies, b) temporal evolution and scientific mapping of the outputs over time, c) trends in the research topics analysis, d) marked journals and citation analysis, and e) competitive countries and dominant institutions to understand the temporal trends of root plasticity during both drought and recovery in the past 120 years. Results Plant physiological factors, especially in the aboveground part (such as “photosynthesis”, “gas-exchange”, “abscisic-acid”) in model plants Arabidopsis, crops such as wheat and maize, and trees were found to be the most popular study areas; they were also combined with other abiotic factors such as salinity, nitrogen, and climate change, while dynamic root growth and root system architecture responses received less attention. Co-occurrence network analysis showed that three clusters were classified for the keywords including 1) photosynthesis response; 2) physiological traits tolerance (e.g. abscisic acid); 3) root hydraulic transport. Thematically, themes evolved from classical agricultural and ecological research via molecular physiology to root plasticity during drought and recovery. The most productive (number of publications) and cited countries and institutions were situated on drylands in the USA, China, and Australia. In the past decades, scientists approached the topic mostly from a soil-plant hydraulic perspective and strongly focused on aboveground physiological regulation, whereas the actual belowground processes seemed to have been the elephant in the room. There is a strong need for better investigation into root and rhizosphere traits during drought and recovery using novel root phenotyping methods and mathematical modeling.